Multi-detector CT in the pre-operative assessment of live donors for liver transplantation - Gupta, Vandana; C. J., Pallavi; Kalyanpur, Arjun; L., Dayananda (International Surgery Journal, 2017)
Background: Transplantation surgeons are now performing living donor liver transplantation because of the severe shortage of cadaveric livers. This study was undertaken to assess the role of 64-slice multidetector CT in the pre op evaluation of living related liver donors for transplantation. Methods: This was a prospective correlation study of 26 patients who were referred to the Department of Radiodiagnosis, Narayana Hrudayalaya, Bangalore for evaluation of living related donors for liver transplantation from March 2008 to May 2009. Results: MDCT has 100% sensitivity, 93.7% specificity in detecting the hepatic arterial anatomy; 100% sensitivity and specificity in detecting portal venous anatomy and its variants, and 93.3% sensitivity and 100% specificity in detecting hepatic venous anatomy. Conclusions: Multi-detector CT is a single comprehensive, non-invasive and accurate imaging modality for pre-operative and postoperative evaluation of liver transplant patient. It allows an accurate assessment of liver parenchyma, hepatic vascular anatomy, graft volume and detection of post-operative complications in donors and recipients of LRLT.